Choreographies of protest performance as recruitment to activism and the movement of perception during the 2015 re-emergence of student activism at Rhodes University - Qoza, Phiwokazi (Rhodes University, Faculty of Humanities, Department of Political and International Studies, 2020)
It has been argued that individuals participate in activism due to an identification with the preferences and interests of an emerging group of actors or in solidarity with a pre-existing network that has resorted to a number of protest repertoires in order to make claims or demands. Additionally, an emerging instance of protest is often linked to an image of previous protest events through the employment of a combination of master frames which function as discursive articulation of the encounter in familiar terms, creating a frame resonance which recruits adherents and constituents. To understand why some bystanders to protest transcended to actors in protest and the development of frames within a protest cycle, a performance ethnography is employed to observe and analyse choreographies of protest which took place at an institution of higher education in South Africa during the 2015 re-emergence of wide-spread student activism. It is found that in encountering an atmosphere of protest there emerged a relation of feeling, referred to as "feeling the vibe or atmosphere" , which those who became protest performers resolved in ways which increased their capacity to act in favour of co-constituting that atmosphere. During the encounter between the bystander body and the atmosphere of protest, non-linear somatic communication, characterised by active and passive gestures and postures, occurred through which protest performers developed contact and connection with other bodies as a result of the displacement of space. This thesis suggests that participation in activism can be about going with the flow of movement in an uncertain and ambiguous moment and is not limited to an identification with the pre-existing organization of preferences and interests as a frame of resonance emerges to signify somatic communication which differentiated bodies in the duration of protest performance. Therefore, this thesis uses the theory of affect to situate student activism in-between the politics of performance and the performance of politics whereupon the rhythm of song creates an opening for the kinaesthetic to create form from spontaneous movement of the body as an event of the movement of perception and the perception of movement.
Keywords: College students -- Political activity -- South Africa; Student protesters -- South Africa; Student movements -- South Africa; Higher education and state -- South Africa; Performance art -- Political aspects -- South Africa; Protest songs -- South Africa